The Health-Care Provider's Perspective of Education Before Kidney Transplantation. (December 2016) - Trivedi, Paraag; Rosaasen, Nicola; Mansell, Holly
Context: Adequate patient education is essential for preparing potential recipients for kidney transplantation. Health-care providers play a vital role in education and can identify gaps in patient understanding. Objective: To identify deficits in patient knowledge from the perspective of a transplant multidisciplinary care team and determine whether their perceptions align with patients who have previously undergone a transplant. Design: An open call was advertised for health-care providers to attend a focus group discussion regarding the educational needs of pretransplant patients in 1 Canadian center. A predetermined, semistructured set of questions was used to collect the views of transplant caregivers. A moderator, assistant moderator, and research assistant facilitated the discussion, which was transcribed verbatim. Paper surveys were distributed to collect opinions of those unable to attend or uncomfortable to voice their opinion in an open forum. Qualitative analysis software was used to identify any emergent themes. Results were compared to a previous study undertaken in transplant recipients. Results: Despite pre- and posttransplant education, specific themes emerged including misconceptions about the assessment process and time on the wait list and the surgery, incongruency between patient expectations and outcome, and confusion regarding medications. Health-care provider perceptions were remarkably consistent with transplant recipients. Conclusion: Health-care providers identified gaps in patient understanding indicating that transplant candidates may not be internalizing what is taught. Innovative educational approaches may be needed to provide more successful patient education. Similarities between health-care provider and patient perceptions suggest that care providers are a valuable source of information.